CORRELATIONS BETWEEN PHYSICAL PROPERTIES AND POINT LOAD STRENGTH INDEX OF PRASINITES: A CASE STUDY FROM EAST ATTICA PREFECTURE - Kotsanis, D.; Nomikos, P.P.; Rozos, D.; Sofianos, A.I. (Bulletin of the Geological Society of Greece, 2016)
The aim of this study is to investigate the statistical correlations between the point load strength index and certain physical properties, e.g. the dry density and the dry longitudinal ultrasonic wave velocity of prasinites (metabasites). Statistically significant correlations established between the physical properties as well as between each physical quantity and the point load strength index. According to bibliography, this is one of the first efforts to develop relations between physical and mechanical properties for this particular petrological type, and therefore the derived equations can be a useful tool to the investigation of these petrological types, either in the study area or in other sites, where prasinites of similar structural characteristics, are examined for the foundation of various constructions.